KOMUNIKASI DAKWAH DALAM BINGKAI TEORI-TEORI PSIKOLOGI - Indah Siti Romadhonah; Malik Ibrahim (Yayasan Nusantara Hasana Berdikari, 2023)
A da'i when he wants to convey a da'wah message certainly wants to get a good response or response from the communicant to the message he conveys. To deliver an effective and maximum message, a da'i must give a da'wah message in accordance with the mental condition or feelings of mad'u at that time. Therefore, one of the fields of science that discusses explaining, predicting, and controlling mental or mental events and mad'u behavior is psychology. This study aims to describe the theories of da'wah psychology. This research uses qualitative research methods with a library research approach. Technical analysis of data in this study is in the form of analysis of a documentation content. This analysis is a way to get the appropriate data. rare then the researcher identifies the data from the bias of the data characteristics, then the information is made systematically so that the object under study is able to provide a perfect conclusion. The research results show that the theories of da'wah psychology include: persuasive theory, learning theory, cognitive dissonance theory, cognitive response theory, planned action theory, Elaboration of Likelihood Model (ELM) theory, and systematic heuristic theory.